Podróż Menelaosa do Indii - Wróbel, Małgorzata (Gajt Wydawnictwo 1991 s.c., 2018)
The article focusses on ancient Greek commentaries to two passages from Homer’s Odysseia 1. 22–24 and 4. 81–89 which are mentioned by Strabo in his Geography. In the first passage Homer refers to Aethiopians who lived on the banks of Oceanus, in the second describes Menelaus’s journey. Strabo discussed two attitudes to that question. The first was the oppinion of the Alexandrine grammarians and their pupils, like Aristarchos of Samotrake, and Apollododus of Athens. This scholars thought, that the Menealus wandering took place only on the Mediterraean Sea. The second oppinion was that of Crates of Mallus, the leader of the literary school and head of the library of Pergamum. In his grammatical exegesis of Homer he stated, that Menelaus could sail to India. Ancient grammarians oppinions were gathered by Aristonicus of Alexandria in a work called On the Wandering of Menelaus, and then epitomized by Strabo (1.2,20;31–35).
Keywords: Strabo; Homer; Crates of Mallus; Aristarchus of Samothrake; Menelaus